A Synthetic SOD/Catalase Mimic Compound for the Treatment of ALS - Matan Soll; Hagit Goldshtein; Ron Rotkopf; Niva Russek-Blum; Zeev Gross (MDPI AG, 2021)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease affecting motor neurons. To date, the etiology of the disease is still unclear, with evidence of reactive oxygen species, mitochondrial dysfunction, iron homeostasis perturbation, protein misfolding and protein aggregation as key players in the pathology of the disease. Twenty percent of familial ALS and two percent of sporadic ALS instances are due to a mutation in Cu/Zn superoxide dismutase (SOD1). Sporadic and familial ALS affects the same neurons with similar pathology; therefore, the underlying hypothesis is that therapies effective in mutant SOD1 models could be translated to sporadic ALS. Corrole metal complexes have lately been identified as strong and potent catalytic antioxidants with beneficial effects in oxidative stress-related diseases such as Parkinson's disease, Alzheimer's disease, atherosclerosis, diabetes and its complications. One of the most promising candidates is the iron complex of an amphiphilic corrole, 1-Fe. In this study we used the SOD1 G93R mutant zebrafish ALS model to assess whether 1-Fe, as a potent catalytic antioxidant, displays any therapeutic merits in vivo. Our results show that 1-Fe caused a substantial increase in mutant zebrafish locomotor activity (up to 30%), bringing the locomotive abilities of the mutant treated group close to that of the wild type untreated group (50% more than the mutated untreated group). Furthermore, 1-Fe did not affect WT larvae locomotor activity, suggesting that 1-Fe enhances locomotor ability by targeting mechanisms underlying SOD1 ALS specifically. These results may pave the way for future development of 1-Fe as a viable treatment for ALS.